Análise da percepção das condições da infraestrutura dos pontos de ônibus oferecida aos usuários : um estudo de caso da cidade de São João da Boa Vista, SP - Bassi Filho, Raphael (2007)
This paper is the result from a research which has been done to identify the importance of the expected attributes inside a bus stop design: which are characterized by a system of information and by its framework (furnishings) which may offer to the passengers appropriate conditions during the time that are waiting to board. The variant which distinguish the attributes from the information system and the furnishings elements from the bus stop were selected from a huge amount of variable list through a bibliographic review. The importance of these variants was determined through the information process which has been gotten from the application of a research with the users of this system using the “Professed Priority Technique”. It was noticed that the bus stop features, which were favorite by the users, must offer safe and comfort conditions (seat with shelters), whose furnishings components refer to; and bus stop identification facilities (place identification advertisement) , when it is approached the information system. Subsequently the users prefer that the bus stop environment arranges others facilities (line identification; outline rout, clock, advertising picture and wastebasket). The final result will be able to contribute to a project definition which are bound for a bus stop betterment, giving a better importance to the increase of this kind of transportation demand.